Detecting anomalies in human eyes using structural similarity index measurement - Jahan, Monwar; Rushu, Fazle Rabbi; Tabassum, Subah; Ferdous, Jannatul (Brac University, 2019)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.